Hubungan Adverse Childhood Experiences (ACEs) Dengan Kecemasan Pada Mahasiswa Program A S1 Keperawatan Universitas Andalas - Wenny, Bunga Permata; Indriani, Zela; Yeni, Fitra (REAL in Nursing Journal, 2022)
Background: Students are one of the groups that are prone to experiencing anxiety psychological problems. Anxiety in students is caused by several factors, one of which is Adverse Childhood Experiences (ACEs). The purpose of this study was to measure the relationship between Adverse Childhood Experiences (ACEs) and anxiety in the Andalas University A S1 student program. Methods: This research is a quantitative study with a correlational design using a cross sectional approach with a sample of 237 respondents who were selected using stratified random sampling according to the inclusion criteria that have been set. The instruments used in this study were Generalized Anxiety Disorder 7 (GAD-7) and Adverse Childhood Experiences International Questionnaire (ACE-IQ). Results: In the univariate analysis, the mean score of ACEs in Andalas University Nursing A S1 students was 2.47 with the highest mean dominance, namely neglect and the average anxiety score for Andalas University Nursing A S1 students was 8.24. Bivariate analysis in this study used the Pearson Product Moment test. Conclusion: The results showed that there was a significant relationship between Adverse Childhood Experiences (ACEs) and anxiety (p-value = 0.000) which had a positive or one-way correlation (r = 0.235) with a weak correlation strength. It is expected that educational institutions will conduct counseling programs and special interventions to prevent and overcome student problems.Keywords: Adverse childhood experiences, ACEs, Anxiety, Students, Nursing